2010
DOI: 10.1086/tcj.64.20749244
|View full text |Cite
|
Sign up to set email alerts
|

Factions and Spoils: Examining Political Behavior Within the Local State in China

Abstract: While students of Chinese politics have long been interested in the impact of fiscal and administrative decentralization on patterns of governance in China, few have examined the impact of decentralization on political dynamics within the local state. Focusing on the county-the level of government primarily responsible for delivering public services, managing local state-owned enterprises, and coordinating the economy-this article explains how the pressures and incentives associated with decentralization have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 1 publication
0
35
0
Order By: Relevance
“…First, the study of local politics and state‐society relations has been overrepresented at the expense of analyses of central government politics and institutions . Questions that became the center of epistemic attention, among several others, explored among other themes, the role of local governments in China's economic and infrastructural development (Oi, ; Ong, ; Looney, ; Montinola et al., ; Shirk, ), economic liberalization and the rise of predatory local states (Ong, ; Pei, ), the characteristics and effects of village elections (Landry et al., ; Li, ; O'Brien, ; O'Brien and Han, ), residents’ committees in urban areas (Read, , ), the cadre evaluation system and its impact on local governance (Edin, ; Kinkel and Hurst, ; Whiting, ), the impact of elite factions on local governance (Hillman, ), and variance in local government responses to contention and collective protests (Cai, , ; Hurst, ), as well as actors involved in and forms of local government repression (Deng and O'Brien, ; O'Brien and Deng, ) . Because most analyses have studied local‐level politics, we still know little about how central and provincial government institutions work and the relations of power among actors between and within those institutions.…”
Section: Regime Constraints and The Study Of Chinese Politicsmentioning
confidence: 99%
“…First, the study of local politics and state‐society relations has been overrepresented at the expense of analyses of central government politics and institutions . Questions that became the center of epistemic attention, among several others, explored among other themes, the role of local governments in China's economic and infrastructural development (Oi, ; Ong, ; Looney, ; Montinola et al., ; Shirk, ), economic liberalization and the rise of predatory local states (Ong, ; Pei, ), the characteristics and effects of village elections (Landry et al., ; Li, ; O'Brien, ; O'Brien and Han, ), residents’ committees in urban areas (Read, , ), the cadre evaluation system and its impact on local governance (Edin, ; Kinkel and Hurst, ; Whiting, ), the impact of elite factions on local governance (Hillman, ), and variance in local government responses to contention and collective protests (Cai, , ; Hurst, ), as well as actors involved in and forms of local government repression (Deng and O'Brien, ; O'Brien and Deng, ) . Because most analyses have studied local‐level politics, we still know little about how central and provincial government institutions work and the relations of power among actors between and within those institutions.…”
Section: Regime Constraints and The Study Of Chinese Politicsmentioning
confidence: 99%
“…Competing with each other in terms of economic success, money, and power makes use of cooperation and so-called helping networks, or guanxi, with the business sector or the central state government in order to achieve political objectives (Martin 2016). In this situation, officials have a large operating space and it is understood that "making money" is something the governments are permitted to do, benefitting is tolerated, and revenues are often used at the discretion of local officials (Hillman 2010). Up to the present time, local politics has been driven mainly by competition over revenue and the search to generate new revenue streams, for the benefit not only of local officials but also for regional infrastructure and welfare projects.…”
Section: China and Corruptionmentioning
confidence: 99%
“…As R. A. W. Rhodes (1981) pointed out in his "power-dependence" model of intergovernmental relations, in these relations, both the dependence between government organisations and the strategies of the "dominant coalitions" within the organisations to regulate the dependence are of particular concern (Rhodes 1981: ch.5), because "noone regulates central-local relations except the participants" (Rhodes 1981: 111). In the case of the Chinese local state, research has, in fact, shown how "factions" (Hillman 2010) and collusion between party and government personnel and their friends and relatives (Smith 2009; Zhou 2010) may influence decision-making.…”
Section: Rural Urbanisation In the Shadow Of Urban Expansionismmentioning
confidence: 99%